2015
DOI: 10.1093/nar/gkv613
|View full text |Cite|
|
Sign up to set email alerts
|

The de-ubiquitylating enzymes USP26 and USP37 regulate homologous recombination by counteracting RAP80

Abstract: The faithful repair of DNA double-strand breaks (DSBs) is essential to safeguard genome stability. DSBs elicit a signaling cascade involving the E3 ubiquitin ligases RNF8/RNF168 and the ubiquitin-dependent assembly of the BRCA1-Abraxas-RAP80-MERIT40 complex. The association of BRCA1 with ubiquitin conjugates through RAP80 is known to be inhibitory to DSB repair by homologous recombination (HR). However, the precise regulation of this mechanism remains poorly understood. Through genetic screens we identified US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 65 publications
6
80
1
Order By: Relevance
“…Another study also used 53BP1 focus formation as a screening readout, and this study found USP26 and USP37 as major antagonists of the IR-induced 53BP1 foci (90). This study found Dub3 and USP44 in the screen, consistent with the other screenings described above.…”
Section: Dubs That Modulate Dsb Repair Signalingsupporting
confidence: 81%
“…Another study also used 53BP1 focus formation as a screening readout, and this study found USP26 and USP37 as major antagonists of the IR-induced 53BP1 foci (90). This study found Dub3 and USP44 in the screen, consistent with the other screenings described above.…”
Section: Dubs That Modulate Dsb Repair Signalingsupporting
confidence: 81%
“…Paradoxically, although DSB loading of 53BP1 and RAP80 underlies robust activation of DNA damage responses (DDRs), they operate at the expense of high-fidelity DNA repair, because their productive accumulation at DSB-flanking chromatin blocks DNA end resection and suppresses RAD51-dependent homologous recombination (HR) repair (4)(5)(6)(7)(8)(9)(10)(11). Exactly how cells achieve a balance between robust DSB signal transduction and HR repair remains to be defined, but several lines of evidence converge on the idea that limiting the extent of DSB ubiquitylation may selectively promote HR repair (12)(13)(14)(15), highlighting the need for cell-intrinsic mechanisms to restrain chromatin responses arising from DSBs (16).…”
mentioning
confidence: 99%
“…A primary level of this regulation is the universal balance between the relevant E3 ligases and opposing deubiquitylating proteases (DUBs) (Pellegrino and Altmeyer, 2016). Interestingly, the DUBs USP26 and USP27 were found to modulate RNF168-mediated protein ubiquitylation at DSB sites thereby preventing excessive spreading of RAP80-BRCA1, promoting association of BRCA1 with PALB2 and streamlining HRR (Typas et al, 2015), similarly to the role we attribute to UBE4A. Another level of regulation is mediated by opposing actions of E3 ligases.…”
Section: Discussionmentioning
confidence: 57%